Respuesta :
Answer:
30b^5 - 20b^3
Step-by-step explanation:
5b^3(6b^2 - 4)
When you multiply numbers with exponents, you add the exponents.
5b^3 * 6b^2 = 30b^5
5b^3 * -4 = -20b^3
30b^5 - 20b^3
Answer:
[tex]30b^5-20b^3[/tex]
Step-by-step explanation:
The distributive property says:
for every a, b, c, [tex]a\cdot (b+c)=a\cdot b+a\cdot c[/tex] (the distributive property over addition)
or [tex]a\cdot (b-c)=a\cdot b-a\cdot c[/tex] (the distributive property over subtraction).
In your case, applying distributive property over subtraction to the expression [tex]5b^3(6b^2-4)[/tex], you get
[tex]5b^3\cdot 6b^2-5b^3\cdot 4=30b^5-20b^3.[/tex]